Managing innovation in educational institutions - Kenny, John (Australasian Journal of Educational Technology, 2002)
Traditionally, project management practices have not drawn any distinction between the characteristics of different projects. Recent research has found that innovative projects require different project management approaches if quality outcomes are to be achieved. Projects involving more innovation require more open management processes and contain a higher percentage of academic and/or professional staff. These characteristics often apply to educational projects in tertiary institutions. There is conflict inherent in managing change projects in educational environments between the classical 'project management' approach and the way that academics and teaching staff, who are independent professionals, traditionally work. This study derived from experience at RMIT, where a system wide online learning system (the Distributed Learning System, DLS) has been implemented since 1999. The implications for the project management approaches suitable for educational projects are discussed and a typology is suggested to categorise projects within an organisation and link them to key factors for successful project management.